Pengaruh Harga dan Kualitas Produk terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan sebagai Variabel Intervening - Asma'ul Khusna, Elda Fitra; Nirawati, Lia (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the effect of price and product quality on customer loyalty through customer satisfaction as an intervening variable on @vivo_indonesia Instagram followers. This type of research is quantitative research, while in this study, the population used is the @vivo_indonesia Instagram account which has 857,171 followers, with the sampling technique using purposive sampling. Data was collected through a questionnaire with descriptive and inferential statistical analysis techniques using the Smart-PLS 4.0 program. Based on the results of this study, it is concluded that price has a positive and significant effect on customer satisfaction. Product quality has a positive and significant effect on customer satisfaction. Customer satisfaction has a positive and significant effect on customer loyalty. Price has a positive and insignificant effect on customer loyalty. Product quality has a positive and significant effect on customer loyalty. Price has a negative and significant effect on customer loyalty through customer satisfaction. Product quality positively and significantly affects customer loyalty through customer satisfaction. Keywords: Price, Product Quality, Customer Satisfaction, Customer Loyalty